Pengembangan Model Pembelajaran Menyenangkan Berbasis Game Interaktif Wordwall pada Materi Membaca Teks Informatif Siswa Kelas 5 SDN Bangbayang 2 - Imas Susilawati; Neng Lies Susilawaty; Elis Hasanah; Siti Ade Amiati; Aan Hasanah; Rosyidatul Munawaroh (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This research aims to develop a fun learning model based on interactive wordwall games on informative text reading material in class V of Bangbayang 2 Elementary School, Cianjur Regency. This type of research is development research (R&D) with the ADDIE model which consists of five steps: analysis, design, development, implementation and evaluation. The designed media is then validated by the validator using a validation sheet in the form of a questionnaire. Product validation consists of material and media experts. To practice product quality, this is done by filling out teacher and student response questionnaires. Then, the effectiveness test is carried out by giving evaluation questions to students. The results of media research obtained a validity level of 86% from the material aspect in the very valid category, 80% from the media aspect in the valid category. Thus, it can be concluded that the learning media in the form of interactive wordwall media using a fun learning model in Indonesian language learning in class V elementary school is declared practical, effective, and suitable for use in learning.